Efektifitas Model Pembelajaran Team Quiz Menggunakan Media Zoom Meting Terhadap Hasil Belajar Siswa - Vera Septi Andrini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
This study aims to determine the effectiveness of the Team Quiz learning model on student learning outcomes. In this study, the research design used a quantitative approach. The population of this study was all eighth grade students of SMP Negeri 3 Nganjuk in the 2019/2020 academic year. The subjects used were mathematics with the Pythagorean Theorem material for class VIII students at SMPN 3 Nganjuk in the 2019/2020 academic year. While the samples used were students in class VIII-E and VIII-H. Data collection techniques using tests, observations, and documentation. The results showed that the experimental class using the Team Quiz model obtained better results than the control class using the conventional method. From the data analysis of the post-test results of the experimental class, the average value = 76.23 of 35 students. While the data of the post-test results for the control class obtained an average value of 58.97 from 35 students. The achievement of student learning outcomes using conventional learning methods is Good Enough. Team Quiz is a learning model that emphasizes teamwork in groups. So that it can make students more motivated and active in learning.